One-repetition-maximum measures or maximum bar-power output: Which is more related to sport performance? - Loturco, I.; Suchomel, T.; Bishop, C.; Kobal, R.; Pereira, L. A.; McGuigan, M. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To compare the associations between optimum power loads and 1-repetition-maximum (1RM) values (assessed in half-squat and jump-squat exercises) and multiple performance measures in elite athletes. Methods: Sixty-one elite athletes (15 Olympians) from 4 different sports (track and field [sprinters and jumpers], rugby sevens, bobsled, and soccer) performed squat and countermovement jumps, half-squat exercise (to assess 1RM), half-squat and jump-squat exercises (to assess bar-power output), and sprint tests (60 m for sprinters and jumpers and 40 m for the other athletes). Pearson product-moment correlation test was used to determine relationships between 1RM and bar-power outputs with vertical jumps and sprint times in both exercises. Results: Overall, both measurements were moderately to near perfectly related to speed performance (r values varying from -.35 to -.69 for correlations between 1RM and sprint times, and from -.36 to -.91 for correlations between bar-power outputs and sprint times; P < .05). However, on average, the magnitude of these correlations was stronger for power-related variables, and only the bar-power outputs were significantly related to vertical jump height. Conclusions: The bar-power outputs were more strongly associated with sprint-speed and power performance than the 1RM measures. Therefore, coaches and researchers can use the bar-power approach for athlete testing and monitoring. Due to the strong correlations presented, it is possible to infer that meaningful variations in bar-power production may also represent substantial changes in actual sport performance.